Increasing the diversity of dietary fibers in a daily-consumed bread modifies gut microbiota and metabolic profile in subjects at cardiometabolic risk. (31st December 2022) - Ranaivo, Harimalala; Thirion, Florence; Béra-Maillet, Christel; Guilly, Susie; Simon, Chantal; Sothier, Monique; Van Den Berghe, Laurie; Feugier-Favier, Nathalie; Lambert-Porcheron, Stéphanie; Dussous, Isabelle; Roger, Loïc; Roume, Hugo; et al.
ABSTRACT: Some cardiometabolic risk factors such as dyslipidemia and insulin resistance are known to be associated with low gut microbiota richness. A link between gut microbiota richness and the diversity of consumed dietary fibers (DF) has also been reported. We introduced a larger diversity of consumed DF by using a daily consumed bread in subjects at cardiometabolic risk and assessed the impacts on the composition and functions of gut microbiota as well as on cardiometabolic profile. Thirty-nine subjects at cardiometabolic risk were included in a double-blind, randomized, cross-over, twice 8-week study, and consumed daily 150 g of standard bread or enriched with a 7-dietary fiber mixture (5.55 g and 16.05 g of fibers, respectively). Before and after intervention, stool samples were collected for gut microbiota analysis from species determination down to gene-level abundance using shotgun metagenomics, and cardiometabolic profile was assessed. Multi-fiber bread consumption significantly decreased Bacteroides vulgatus, whereas it increased Parabacteroides distasonis, Fusicatenibacter saccharivorans, an unclassified Acutalibacteraceae and an unclassified Eisenbergiella (q < 0.1). The fraction of gut microbiota carrying the gene coding for five families/subfamilies of glycoside hydrolases (CAZymes) were also increased and negatively correlated with peaks and total/incremental area under curve (tAUC/iAUC) of postprandial glycemia and insulinemia. Compared to control bread, multi-fiber bread decreased total cholesterol (−0.42 mM; q < 0.01), LDL cholesterol (−0.36 mM; q < 0.01), insulin (−2.77 mIU/l; q < 0.05), and HOMA (−0.78; q < 0.05). In conclusion, increasing the diversity of DF in a daily consumed product modifies gut microbiota composition and function and could be a relevant nutritional tool to improve cardiometabolic profile.